Experimental Investigation on the Concentric and Nonconcentric Waste Heat Recovery Device - Zhang Zhenglai; Han Xiaoxing; Wang Yaxiong; WuWei; Li Penghui (Zhileng xuebao)
A series of tests were carried out on a new structure of heat pipe exchanger. It uses acetone as working fluid. The investigation was conducted at different heat loads, the tilt angles of device are 30°、45°、60°、75°、90°and the charging ratio of working fluid is 30%. The angles, length and operation temperature was adjusted in the test to investigate the thermal performance and effectiveness of heat recovery system. It reveals that the maximum heat transport increases with the augment of the operation temperature, evaporation length. Eventually, the experimental data showed that the optimum operating angle is 60°with evaporation length of 270 mm.